NUTRITION EDUCATION WITH COOKING DEMONSTRATION FOR HEAD START PARTICIPANTS IN RILEY COUNTY - Frans, Nike (My University, 2017)
This field experience is a collaboration work with Riley County K-State Research and Extension Office. A series of four nutrition education classes was designed and delivered to the parents of under five children participated in Head Start program in Riley County, Kansas. The main goal of this field experience project is to improve parents’ knowledge and understanding about healthy food and healthy eating for their children, as well as to promote home-cooked meals and cooking confidence among parents. Social cognitive theory was used to guide the process of this program from planning, implementation, and evaluation. Self-efficacy, outcome expectation, knowledge, observational learning, and behavioral skills were the constructs of social cognitive theory that became the main focus of this program. The topic of each class was different, covering healthy food and healthy eating, eating healthy on a budget, healthy drinks, healthy snacks, and picky eating. There was a cooking demonstration in each class to promote cooking confidence of the parents. Several strategies were incorporated, including repetitively exposing the participants about simple and important nutrition messages and encouraging parents’ participation in class. There were three types of evaluation, including cooking skills evaluation, knowledge evaluation, and program evaluation. At the end of the program, parents showed improvements on their cooking confidence and knowledge about nutrition, and improvements on the awareness of healthy food choice.
Keywords: Nutrition Education; Cooking Demonstration; Social Cognitive Theory; Estension Office; Head Start